Notary Deeds as Evidence in Civil Courts: Proof Strength and Notary Responsibility Due to Cancellation of Deeds by The Court in Indonesia - Sri Iin Hartini; Salesius Jemaru; Edward Edward (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
A notarial deed is written evidence that has the status of an authentic deed and has perfect evidentiary power as regulated in Article 1868 of the Civil Code in conjunction with Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary. In civil court practice, a notarial deed is often used as the main evidence to resolve civil disputes because it is considered to contain external, formal, and material truth. This article aims to analyze the evidentiary power of a notarial deed as evidence in civil courts and to formulate the parameters of a notary's responsibility after the deed is annulled by the court. The research uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach, with primary, secondary, and tertiary legal materials analyzed qualitatively and descriptively. The results of the study indicate that the evidentiary power of a notarial deed is perfect but not absolute, because the court still has the authority to assess the formal and material validity of the deed based on the facts revealed in court so that the deed can remain valid, be degraded to a private deed, or be declared null and void. The notary's responsibility does not arise automatically from every cancellation of the deed, but can only be imposed if there is evidence of error, negligence, or abuse of authority committed by the notary in carrying out his/her duties, while cancellations caused by false statements or documents from the parties are the responsibility of the parties concerned.